(3ELGRI ef TeS GdOjf GdHGHdi ddhRjQ CMeO HGTGs - (3TeS GdOjf CHh YHO Gddg eMeO Hf NdjaI Hf SYO GdOjf GdeQMhej GdThHQj GdTGaYj, GdThHQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY Yed GdYdeGA hLYd ENdGUge ddbHhd SfOG hCHbi MOjKge YGdi GdESfGO Ydi eQ GdOghQ CHOG s
(3BNQgG (B:s
(3hGdMeO ddg hMOg hUdi Gddg Ydi ef dG fHi HYOg s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdELGRI ePjdI HMOjK GdLSGSI dJdejM GdTjN dg ai GdELGRI hecGJHI Hjf GdhRjQ hGdTjN GdHGHdi hLGhH GdTjN Ydjg LeY Pdc cdg eMeO Hf NdjaI GdThHQi ef U (B32 (3Edi U (B42s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs